The Consequences of Sex Recession in Indonesian Marriage Law Perspective - Zakaria, Nursusilawati; Kasim, Nur Mohamad; Towadi, Mellisa (Universitas Negeri Gorontalo, 2024)
This article aims to find out and describe the legal consequences of the sex recession in Indonesia from the perspective of marriage law. The research method used in this study is the normative research method with a literature study approach. The results of this study indicate that marriage recession is a phenomenon and is a necessity in marriage law in Indonesia. When referring to the legal basis of marriage and in the compilation of Islamic law, there is no prohibition on delaying marriage based on the reasons for one's self-development. However, this will impact the legal condition of marriage in Indonesia in the future. Referring to the marriage law and the compilation of Islamic law, the term postponement of marriage is not explicitly mentioned. It is more about preventing marriage. In the Marriage Law, the Prevention of Marriage is regulated in III, which consists of Article 13 to Article 21. Meanwhile, in the compilation of Islamic law, marriage prevention is regulated in Chapter X, divided from Article 60 to Article 69.